What research impacts do Australian primary health care researchers expect and achieve? - Reed Richard L; Kalucy Elizabeth C; Jackson-Bowers Eleanor; McIntyre Ellen (BMC, 2011)
Abstract Background Funding for research is under pressure to be accountable in terms of benefits and translation of research findings into practice and policy. Primary health care research has considerable potential to improve health care in a wide range of settings, but little is known about the extent to which these impacts actually occur. This study examines the impact of individual primary health care research projects on policy and practice from the perspective of Chief Investigators (CIs). Methods The project used an online survey adapted from the Buxton and Hanney Payback Framework to collect information about the impacts that CIs expected and achieved from primary health care research projects funded by Australian national competitive grants. Results and Discussion Chief Investigators (CIs) provided information about seventeen completed projects. While no CI expected their project to have an impact in every domain of the framework used in the survey, 76% achieved at least half the impacts they expected. Sixteen projects had published and/or presented their work, 10 projects included 11 doctorate awards in their research capacity domain. All CIs expected their research to lead to further research opportunities with 11 achieving this. Ten CIs achieved their expectation of providing information for policy making but only four reported their research had influenced policy making. However 11 CIs achieved their expectation of providing information for organizational decision making and eight reported their research had influenced organizational decision making. Conclusion CIs reported that nationally funded primary health care research projects made an impact on knowledge production, staff development and further research, areas within the realm of influence of the research team and within the scope of awareness of the CIs. Some also made an impact on policy and organizational decision-making, and on localized clinical practice and service delivery. CIs reported few broader economic benefits from their research. Routine use of an instrument of this type would facilitate primary health care research funders' determination of the payback for funding of research in this sector.